Osadnictwo późnomeozolityczne na stanowisku 29 w Kopanicy, gm. Siedlec - Bobrowski, Przemysław; Sobkowiak-Tabaka, Iwona (Folia Praehistorica Posnaniensia, 2016)
Kopanica, site 29, is situated on the eastern edge of a former glacial trough, which now channels the Obra River north, and the latitudinal Warsaw-Berlin ice marginal valley. 2003 archaeological excavations at the site revealed evidence of intensive Late Mesolithic settlement. Trenches located on the sandy and gravel fluvial terrace of the Obra and in the zone of biogenic sediments yielded a substantial flint assemblage and remains of a dwelling structure sunken into the ground. The structure was radiocarbon dated owing to a fragment of a burnt animal bone from the fill deposit. The radiocarbon date coincides with the results of technological and typological analyses of the flint inventory. The Mesolithic settlement at the site can accordingly be attributed to a stay of a group representing the Chojnice–Pieńków (post-Maglemose) culture in the second half of the Atlantic period.